SOCIAL ENTREPRENEURSHIP IN CURRAL DE CIMA: PERSPECTIVE OF INNOVATION AND COMMUNITY TRANSFORMATION : Perspective on innovation and community transformation - Nascimento, Tiago; Mendonça dos Santos, Laís (Revista e-TECH: Tecnologias para Competitividade Industrial - ISSN - 1983-1838, 2025)
This analysis, which adopts a dissertation-argumentative methodology, aimed to investigate the main individual contributions of these entrepreneurs, as well as the difficulties they faced throughout their journeys. The research identified numerous challenges related to health, economic inequality, and the absence of public-private institutional support. Entrepreneur A (a mason and metalworker) demonstrated innovation in his segment. Entrepreneur B (a public servant) promoted quality education in basic education. Entrepreneur C (a student of Administration) sought to apply the knowledge acquired from the perspective of UFPB, Campus IV – Litoral Norte. The theme encompasses community engagement, the role of sustainable entrepreneurship, and relevant contemporary issues. The results indicate the importance of the articulation between purpose, management, and social impact, with an emphasis on the practical use of technology in contexts of vulnerability. The study contributes to the academic debate in Applied Social Sciences, providing support for researchers and professionals interested in entrepreneurship, environmental causes, and technological innovation.